The use of nd:yag laser on permanent molar with periapical lesions, two year follow up - Kalyoncu, Işıl Özgül; EğilL, Edibe; Tanboğa, İlknur (My University, 2013)
It is considered that Nd:YAG (1,064 nm) laser has a bactericidal effect against bacteria to a depth of 1.000 μm. The aim of the study was to assess the efficacy of Nd:YAG laser irradiation on permanent molar root canal disinfection and follow up of the healing process. The Nd:YAG laser system, emitting at a wavelength of 1064 nm, was applied for 46 and 36 numbered root canal for three times (1.5 W, 15 Hz, 5s) in working length of a 10-year-old girl patient with caries cavities extended to the pulp and extensive periapical radiolucency. At the third session of Nd:YAG laser application the patient was asymptomatic. After two years, the clinical and radiographic follow up revealed that the patient was asymptomatic and the periapical tissues and restored tooth were healthy. The Nd:YAG laser irradiation is not an alternative but a possible supplement to existing protocols for root canal disinfection.
Keywords: bacterial elimination, chronic periapical lesions, Nd:YAG laser, pediatric dentistry, permanent molars.